2022
DOI: 10.3390/su14042234
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Lost Safety Benefits of ADAS Technologies Due to Inadequate Supporting Road Infrastructure

Abstract: Advanced driver assistance systems (ADAS) provide warnings to drivers and, if applicable, intervene to mitigate a collision if one is imminent. Autonomous emergency brakes (AEB) and lane keep assistance (LKA) systems are mandated in several new vehicles, given their predicted injury and fatality reduction benefits. These predicted benefits are based on the assumption that roads are always entirely supportive of ADAS technologies. Little research, however, has been conducted regarding the preparedness of the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Adaptive cruise control systems also assist drivers in keeping a safe headway. However, these will also be reliant upon appropriate infrastructure (Peiris et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive cruise control systems also assist drivers in keeping a safe headway. However, these will also be reliant upon appropriate infrastructure (Peiris et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the third test route was a portion of the WMU campus drive with a low curvature. It has been observed that there is a notable difference in the performance of vehicle automation products on arterial roads with steep road curvatures, uneven road surface finish, improper lane markings, and lane marking obstructions [30]. The CERPM technology can be tested to address these drawbacks.…”
Section: Test Routesmentioning
confidence: 99%
“…As an example, it is worth noting that forwardcollision warning systems encounter challenges in detecting objects while a vehicle is in motion at elevated velocities. However, four of these technologies are particularly noteworthy in terms of the difficulties they pose, namely processors, sensors, software algorithms, and mapping [3][4][5][6].…”
Section: Key Aspects Of Adasmentioning
confidence: 99%